Yuri Sopov in the Siberian Newspaper Zarya (1919) - Elena Yu. Kulikova (Studia Litterarum)
The article examines three poems by Yuri Sopov published in Siberian daily socio-political and literary newspaper Zarya from the state archive of Novosibirsk region. Yuri Sopov was an Omsk poet who lived a short life (1897–1919): he prematurely died as the result of the explosion in the courtyard of A.V. Kolchak’s house. Sopov wrote series of poems, the rhymed Tale of the Last Summer, and the unfinished poem about Arthur Rimbaud only fragments of which have remained. The article focuses on Sopov’s poems “Sunset at the River,” “Love,” and “Loneliness” from his books Evenings at the River and I Remember the Early Mass... The latter and “Sunset at the River” are published in this article for the first time since 1918–1919. The poet retreats to the world of dreams and slumber that was typical for Romantic and Symbolist poetry. The “Sunset at the River” and “Love” are shaped after Balmont’s “Moisture” and correspond to the Symbolist tradition of the so-called “boat” poetry. “Loneliness” is a text that echoes political events that took place in Russia of that time. In the poem “I remember the early mass...,” Sopov borrows from both Klyuev and Blok, combining religious motifs from the former and the motif of the “beautiful lady” from the latter; at the same time, the poem has a distinct Akmeistic subtext inspired by Akhmatova and Mandelstam.